1978
DOI: 10.1007/bf00493544
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycinuria with nephrolithiasis

Abstract: The case of a seven and a half-year-old girl with hyperglycinuria, oxalate nephrolithiasis, and a normal plasma amino acid pattern is presented. Hyperglycinuria amounted to 400 mg of glycine in 24 h urine and the stone was composed of calcium oxalate dihydrate. The metabolic relationship between glycine and oxalate is discussed. It is possible that the association of nephrolithiasis and hyperglycinuria was coincidental, although the case of familial hyperglycinuria with nephrolithiasis reported by De Vries and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Some obligate heterozygotes for familial iminoglycinuria are incompletely recessive and exhibit isolated hyperglycinuria without iminoaciduria. Hyperglycinuria without iminoaciduria can also be a feature of a K m variant of familial iminoglycinuria, 93 as well as dominantly inherited renal hyperglycinuria with nephrolithiasis (MIM 138500) 94 and autosomal dominant glucoglycinuria (MIM 138070). 95 Glycinuria without glycinemia can also occur in urinary tract infections or contaminated urine samples as a result of bacterial hydrolysis of glycine conjugates excreted in urine.…”
Section: Renal Hyperglycinuriamentioning
confidence: 99%
“…Some obligate heterozygotes for familial iminoglycinuria are incompletely recessive and exhibit isolated hyperglycinuria without iminoaciduria. Hyperglycinuria without iminoaciduria can also be a feature of a K m variant of familial iminoglycinuria, 93 as well as dominantly inherited renal hyperglycinuria with nephrolithiasis (MIM 138500) 94 and autosomal dominant glucoglycinuria (MIM 138070). 95 Glycinuria without glycinemia can also occur in urinary tract infections or contaminated urine samples as a result of bacterial hydrolysis of glycine conjugates excreted in urine.…”
Section: Renal Hyperglycinuriamentioning
confidence: 99%
“…De Vries et al 12 reported a case of hereditary glycinuria and recurrent nephrolithiasis in a 20-year-old Bulgarian woman with a history of osteoporosis. Oberiter et al 2 reported another case of glycinuria and nephrolithiasis in a seven and half-year-old girl. Osteoporosis was not reported in the child, but bone diagnostics may have been limited due to available methodologies and the age of their patient.…”
Section: Discussionmentioning
confidence: 99%
“…Glycinuria or hyperglycinuria is a rare disorder with few case reports reported in the literature 1 2. Glycinuria may result either due to a defect in glycine metabolism or to a disturbance of renal reabsorption of glycine 1 2. Typically, glycinuria is encountered as part of other aminoacidurias as in Fanconi syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycinuria usually results from a defect in glycine metabolism or a disturbance in renal tubular reabsorption of glycine [ 4 ]. In some patients, factors such as high-glycine diet or total parenteral nutrition can increase glycine levels in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycinuria is commonly shown as either sole hyperglycinuria or involvement of multiple aminoacidurias relevant to proline and hydroxyproline excretion [ 3 ]. Although the underlying cause of congenital disorders associated with amino acid transport may be benign, hyperglycinuria usually has extensive characteristics related to kidney stones [ 4 ].…”
Section: Introductionmentioning
confidence: 99%